The Role of Economic Status and Environmental Factors in Early Childhood Cognitive Development: Systematic Literature Review and Bibliometric - Nur Afifah Sulaiman; Melly Latifah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Low socioeconomic status (SES) significantly affects adolescents’ cognitive development, influenced by factors like stress, parental education, and limited resources. This study explores themes and publication trends related to SES and cognitive development using a systematic literature review (SLR) and bibliometric analysis (BA). Data from Scopus were analyzed with VOSviewer and Microsoft Excel. A total of 26 peer-reviewed articles were reviewed using statistical methods. Findings show that variables like BMI, household income, parental education, brain structure, and family background positively correlate with cognitive development. In contrast, depression, trauma, puberty, and disciplinary history negatively impact it. Bibliometric analysis reveals a shift from general child development research to more focused areas like executive function and prenatal influences, showing strong ties between SES and cognitive development.